The Influence of Work Motivation, Work Environment, Work Culture on Employee Performance (Case Study at the Bengkulu City Trade and Industry Service) - Fery Irawan (Yayasan Darussalam Bengkulu, 2024)
In limiting the scope of this research, the author focuses only on the influence of work motivation, work environment and work culture on the performance of employees in the Bengkulu City Trade and Industry Department. The research object is permanent employees of the Bengkulu City Trade and Industry Department. The type of research used in this research is explanatory research. Based on the results of research on work motivation variables, it can be concluded that partially work motivation variables influence employee performance. The T-test value for Work Motivation (X1) is 11.995 > 1.673 with a sig value of 0.000 > 0.05, so H0 is rejected and H1 is accepted. Regarding work environment variables, it can be concluded that partially work environment variables influence employee performance. The T-test value for the Work Environment (X2) is 2.683 > 1.673 with a sig value of 0.010 > 0.05, so H0 is rejected and H1 is accepted. Regarding the work culture variable, it can be concluded that the work culture variable partially influences employee performance. The T-test value for Work Culture (X3) is 3.220 > 1.673 with a sig value of 0.002 > 0.05, so H0 is rejected and H1 is accepted. Regarding the variables of work motivation, work environment and work culture, it can be concluded that simultaneously the variables of work motivation, work environment and work culture influence employee performance. The Fcount test result was 55.363, while the Ftable value was used at a significance level of 5% with df= n-k (59-3-1=55) so that an Ftable of 2.01 was obtained. meaning that work motivation (X1), work environment (X2), work culture (X3) have a significant effect on employee performance (Y).